The efficacy of mobile health in alleviating risk factors related to the occurrence and development of coronary heart disease: A systematic review and meta‐analysis. Issue 5 (16th March 2021) - Xu, Yue; Ye, Hui; Zhu, Yuan; Du, Shizheng; Xu, Guihua; Wang, Qing
Abstract: The association between the efficacy of mobile health and the occurrence and development of coronary heart disease (CHD) is still unclear. Mobile health can alleviate the risk factors for CHD. PubMed, EMbase, Web of Science, The Cochrane Library, CNKI, WanFang, and VIP databases were searched from inception through May 28, 2020. Randomized controlled trials of the effect of mobile health in alleviating the risk factors of CHD's occurrence and development were included. Risks of bias were assessed by two independent reviewers by using the RevMan 5.3, GRADEpro, and RoB2.0 to generate findings. Meta‐analyses were performed to investigate the effects of mobile health on risk factors for CHD. Subgroup analyses were conducted. Sixteen randomized controlled trials, including 3898 patients with CHD, were included. Meta‐analysis results showed that mobile health can reduce BMI (mean difference [MD] = − 1.24, 95% CI = − 2.02 to − 0.45, p < .05), waist circumference (MD = − 4.40, 95% CI = − 4.72 to − 4.08, p < .00001), total cholesterol (TC) level (MD = − 0.43, 95% CI = − 0.64 to − 0.22, p < 0.00001), low‐density lipoprotein cholesterol (LDL‐C) level (MD = − 0.31, 95% CI = − 0.48 to − 0.15, p < .05), diastolic blood pressure (MD = − 2.01, 95% CI = − 3.40 to − 0.623, p < .05), and depression (MD = − 8.32, 95% CI = − 12.83 to − 3.81, p < .05) and increase high‐density lipoprotein cholesterol level (MD = 0.16, 95% CI = 0.01 to 0.32, p < .05) with statistically significant differences. The results of subgroup analyses indicated that the simple mobile health intervention has more remarkable advantages in reducing BMI, TC, LDL‐C, and systolic blood pressure than the complex mobile health intervention. Mobile health can alleviate the risk factors for CHD and has a certain effect on the prevention and recovery of CHD. Simple mobile health has a remarkable advantage. Limited by the quantity and quality of included studies, future research enrolling high‐quality studies should be taken to verify the above conclusions.